ESTUARINE OCEANOGRAPHY OF THE VEMBANAD LAKE PART III: THE REGION BETWEEN COCHIN AND THE 3 0 M DEPTH OFF PORTMOUTH - Ramamirtham, C P; Muthusamy, S; Khambadkar, L R; Nandakumar, A; Kunhikrishnan, N P; Murty, A V S (Indian Journal of Fisheries, 2011)
The time-distribution patterns of temperature, salinity and oxygen contentalong the shipping channel from inside the port to a distance of about 15km out into the Arabian sea during 1981-1983 are presented and discussed in thisthird and last part of the estuarine oceanographic study of the Vembanad lake.The distribution patterns show that hydrologically the nearshore region up to 12or 15 km off Cochin is more or less identical to the adjacent coastal region,without having any apparent influence of the lake, during the dry months Januaryto May. During the wet months, however, the discharge from the lake, characterizedby suspended sediments, spreads as a plume, over highly saline and coldupwelled water, turning the region into an intermittent estuary. Though the endof the plume can often be pinpointed around the 30in depthline, by a sharpchange of colour and filaments formed of floating objects of land and freshwaterorigin, the presence of an actual plume front is doubtful because of the weaksurface convergence then occurring in a broad area off Cochin.